Analysis of the Relationship between Thermal Comfort Levels and Green Open Space in Semarang City, Using the Humidex Method - Faridatussafura, Nurzaka; Yulfiah, Yulfiah (Journal of Earth and Marine Technology (JEMT), 2024)
The rapid urban development has increased the density of buildings and decreased the Green Open Space (RTH), thereby affecting the thermal comfort of an area. The level of thermal comfort can be observed from the characteristics of temperature and humidity. The determination of thermal comfort levels, especially in Semarang City, is conducted using the Humidex method. The calculation results show Humidex values ranging from 38.83°C to 41.10°C, categorized as uncomfortable to very uncomfortable. The highest Humidex value was recorded at the Semarang Climatology Station in 2023, while the lowest was at the Ahmad Yani Semarang Meteorology Station in the same year. Meanwhile, Landsat 8 imagery analysis shows that from 2014 to 2023, the total land cover transition in Semarang reached 68.541 km² for buildings; 63.104 km² for tree vegetation; 1.353 km² for other vegetation; and 6.784 km² for water bodies. By the end of the research period in 2023, the area of tree vegetation in Semarang City was 91.187 km². The analysis of the relationship between Humidex values and the area of building cover shows a correlation coefficient of 0.87, indicating an increase in building cover area that has raised the Humidex value in Semarang City. Furthermore, the correlation of Humidex with the area of RTH is -0.83, meaning there is a strong negative linear relationship between the Humidex values and the RTH area, or the larger the RTH cover, the lower the Humidex value in Semarang City. To maintain or improve the level of thermal comfort in Semarang City, it is recommended to balance the distribution of RTH locations, especially in the northern and eastern parts of Semarang. The Semarang City government should enhance the quality of RTH by choosing appropriate vegetation, performing regular maintenance, improving facilities and services around RTH, and continuously educating the public.